2016
DOI: 10.1093/jjco/hyv215
|View full text |Cite
|
Sign up to set email alerts
|

Ability of contrast-enhanced ultrasonography to determine clinical responses of breast cancer to neoadjuvant chemotherapy

Abstract: Objective: We aimed to determine whether contrast-enhanced ultrasonography can predict the effects of neoadjuvant chemotherapy on breast cancer. Methods: The clinical responses of 63 consecutive patients with breast cancer (T1-4, N0-1, M0) to neoadjuvant chemotherapy between October 2012 and May 2015 were assessed using contrastenhanced magnetic resonance imaging, positron emission tomography/computed tomography and contrast-enhanced ultrasonography. Perfusion parameters for contrast-enhanced ultrasonography w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
36
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(40 citation statements)
references
References 34 publications
(40 reference statements)
3
36
0
1
Order By: Relevance
“…This result is consistent with other studies [96,97]. CEUS also achieved high accuracy in predicting the heterogeneity of the response of breast cancer to neoadjuvant chemotherapy [98,99]. The use of microbubbles labeled by specific antibodies also allows CEUS to achieve the level of detail of molecular imaging.…”
Section: Ultrasoundsupporting
confidence: 90%
“…This result is consistent with other studies [96,97]. CEUS also achieved high accuracy in predicting the heterogeneity of the response of breast cancer to neoadjuvant chemotherapy [98,99]. The use of microbubbles labeled by specific antibodies also allows CEUS to achieve the level of detail of molecular imaging.…”
Section: Ultrasoundsupporting
confidence: 90%
“…The ability of CEUS to predict a pathological complete response in patients with breast cancer who have received NAC has been reported previously [20 -25]. In a study of 63 patients, Amioka et al [20] reported that both the peak intensity and the ascending slope were significantly lower in those who achieved a pathological complete response than in those who did not. However, unlike in our study, Amioka et al performed CEUS after completing four cycles of NAC and placed the ROI at the largest tumor contour.…”
Section: Discussionmentioning
confidence: 55%
“…These changes may occur earlier than a reduction in tumor size. Nonetheless, previous reports have not fully evaluated the reproducibility of CEUS [17,20,21,23,25] and debate persists regarding the most appropriate region of interest (ROI) for quantitative analysis of the time-intensity curve (TIC) [9,21,24].…”
Section: Introductionmentioning
confidence: 99%
“…The ability of CEUS to predict a pathological complete response in patients with breast cancer who have received NAC has been reported previously [20][21][22][23][24][25]. In a study of 63 patients, Amioka et al [20] reported that both the peak intensity and the ascending slope were significantly lower in those who achieved a pathological complete response than in those who did not. However, unlike in our study, Amioka et al performed CEUS after completing four cycles of NAC and placed the ROI at the largest ▶ Fig.…”
Section: Discussionmentioning
confidence: 67%
“…The reason for performing the second CEUS examination after the first cycle was that prediction of the response at an early time point is important for treatment modification in non-responders [3,4]. Several studies have evaluated the ability of CEUS to predict early response to NAC [20][21][22][23][24][25]. CEUS is superior to conventional imaging methods when measuring angiogenic changes as an indicator of response.…”
Section: Introductionmentioning
confidence: 99%